Early Enzyme Replacement Therapy Improves Hearing and Immune Defects in Adenosine Deaminase Deficient-Mice - Xu, Xiaobai; Negandhi, Jaina; Min, Weixian; Tsui, Michael; Post, Martin; Harrison, Robert V.; Grunebaum, Eyal (Frontiers in Immunology, 2019)
Background: Inherit defects in adenosine deaminase (ADA) cause severe immune deficiency, which can be corrected by ADA enzyme replacement therapy (ERT). Additionally, ADA-deficient patients suffer from hearing impairment. We hypothesized that ADA-deficient (-/-) mice also exhibit hearing abnormalities and that ERT from an early age will improve the hearing and immune defects in these mice. Methods: Auditory brainstem evoked responses, organ weights, thymocytes numbers and subpopulations, lymphocytes in peripheral blood as well as T lymphocytes in spleen were analyzed in ADA-/- and ADA-proficient littermate post-partum (pp). The cochlea was visualized by scanning electron microscopy (SEM). The effects of polyethylene glycol conjugated ADA (PEG-ADA) ERT or 40% oxygen initiated at 7 days pp on the hearing and immune abnormalities were assessed. Results: Markedly abnormal hearing thresholds responses were found in ADA-/- mice at low and medium tone frequencies. SEM demonstrated extensive damage to the cochlear hair cells of ADA-/- mice, which were splayed, short or missing, correlating with the hearing deficits. The hearing defects were not reversed when hypoxia in ADA-/- mice was corrected. Progressive immune abnormalities were detected in ADA-/- mice from 4 days pp, initially affecting the thymus followed by peripheral lymphocytes and T cells in the spleen. ERT initiated at 7 days pp significantly improved the hearing of ADA-/- mice as well as the number of thymocytes and T lymphocytes, although not all normalized. Conclusions: ADA deficiency is associated with hearing deficits and damage to cochlear hair cells. Early initiation of ERT improves the hearing and immune abnormalities.